ANALISA FINANSIAL PROYEK PEMBANGUNAN JALAN TOL AA DI JAWA TIMUR - Kusuma, Marjono, Fauziah S.C.S Maisarah, Adham Indra (Prokons: Jurnal Teknik Sipil, 2015)
One attempt to create a good transport system is the construction of new roads toll roads. A toll road construction soon to be implemented is AA segment a which is of ?investment oriented and expected to give profits to the investors. According to the plan, the toll road is 40.5 km long development is divided into 4 sections. Data required to perform financial analysis is the cost of investment, operation and maintenance cost, traffic volume, and the toll rate plans. These data to find the values of the parameters used to calculate the financial analysis include the Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The financial analysis will use two funding alternatives, alternative I using 100% equity, alternative II using 30% equity and 70%? loan. The purpose of this study is to determine the results of the financial analysis of the parameter values of highway construction project feasibility and determine the most influential factors after a sensitivity analysis has been made. Based on the financial analysis the investment cost results in IDR 3,827,698,222,645. The financial analysis NPV parameters alternative I results in IDR 661,439,934,962 and alternative II in IDR 230,334,925,350 which means they are feasible because both NPVs are greater than 0; both the IRR of 14.18% for alternative I and 13.02% for alternative II are greater than Minimum Attractive Rate Of Return (MARR) value of 12.42%; so, they are feasible; the value of BCR of alternative I is of 1.13 and alternative II is of 1.04; so, they are feasible because the value of BCR is greater than 1. While the PP of alternative I in the period of 12.1 years and alternative II in the period of 13.5 years. The sensitivity analysis of alternatives I and II result in? the most influential alternative?when construction period experiences ? 3 years backwards.Keywords: investment cost, financial analysis, sensitivity analysis.